2014
DOI: 10.1517/14740338.2014.942219
|View full text |Cite
|
Sign up to set email alerts
|

Patient reports of the frequency and severity of adverse reactions associated with biological agents prescribed for psoriasis in Brazil

Abstract: Biologic agents were associated with high rates of ADRs and SAEs. The data suggests that for patients taking a biologic agent to treat psoriasis and who have one or more comorbidities, warnings of possible adverse events and enhanced surveillance are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 38 publications
(38 reference statements)
1
9
0
Order By: Relevance
“…In Brazil, ANVISA made the decision to suspend marketing in the same year. Before efalizumab was removed from the Brazilian market, a biological drug safety study had reported that 44.2% of patients receiving this drug discontinued the treatment due to serious adverse reactions …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Brazil, ANVISA made the decision to suspend marketing in the same year. Before efalizumab was removed from the Brazilian market, a biological drug safety study had reported that 44.2% of patients receiving this drug discontinued the treatment due to serious adverse reactions …”
Section: Discussionmentioning
confidence: 99%
“…Before efalizumab was removed from the Brazilian market, a biological drug safety study had reported that 44.2% of patients receiving this drug discontinued the treatment due to serious adverse reactions. 39 The research and development of new biological medicines are a growing trend. 10 As in other countries, biologicals accounted for a quarter of the new drugs registered in Brazil between 2003 and 2013 and gave rise to more than 30% of PMSEs.…”
Section: Discussionmentioning
confidence: 99%
“…The safety profiles of IFX treatment in patients with rheumatic diseases has been verified by registries in many countries . However, only a few studies including several hundreds of psoriasis patients reported about the safety and efficacy of IFX treatment in real‐world clinical practice …”
Section: Discussionmentioning
confidence: 99%
“…21 However, only a few studies including several hundreds of psoriasis patients reported about the safety and efficacy of IFX treatment in real-world clinical practice. [22][23][24][25][26][27] In addition, the safety and efficacy profiles of IFX in realworld clinical practice for treating Japanese psoriasis patients remain unclear, because a clinical trial on the safety and efficacy of IFX involved only 114 psoriasis patients. 14,15 We conducted a large-scale, prospective PMS to evaluate the safety and efficacy of IFX treatment, which enrolled all patients treated with IFX, and this study clarified the safety profiles and efficacy of IFX treatment in Japanese psoriasis patients.…”
Section: Discussionmentioning
confidence: 99%
“…New technologies are registered based on controlled and randomized clinical trials, in which, in most cases, they fail to capture important safety results that only appear in real-life studies ( Lopes et al., 2014 ; Fulone et al., 2018 ; De Carmago et al., 2019 ). In addition, in the case of new cancer medicines, often licensed on the basis of limited information, which can cause concern and wasted resources ( Pontes et al., 2020 ).…”
mentioning
confidence: 99%